Business goals, user needs, and requirements: A problem frame‐based view. Issue 3 (17th September 2012) - Lavazza, Luigi
Abstract It is well known that the analysis of requirements involves several stakeholders and perspectives. Very often several points of view at different abstraction levels have to be taken into account: all these features make requirements analysis a complex task. Such intrinsic complexity makes it difficult to understand several of the basic concepts that underlie requirements engineering. Actually, there is some confusion – especially in industry – about what really a user requirement is, what are the differences between user requirements and user needs, and what are their relationships with business processes. The paper aims at clarifying the aforementioned issues, by providing a systematic and clear method for establishing requirements hierarchies. The problem of describing requirements hierarchies is tackled using the problem frames concepts and notation. A case study is used throughout the paper to illustrate the proposed approach. The description of requirements at different levels of abstractions and requirements hierarchies are illustrated. The resulting models are coherent with the reference model for requirements specifications and the problem frames. An analysis process that is aware of the differences between user needs and requirements is also provided, to illustrate the process of refining high‐level goals into requirements that can be satisfied by a hardware/software machine. The proposed method appears promising to model, study, and evaluate the relationships between business processes and the strategies for achieving business goals based on the usage of information technology.